Success factors of small and medium enterprises in the Malaysian furniture industry: discerning the growth of entrepreneurs - Ratnasingam, J.; Ab Latib, H.; Mariapan, M.; Othman, K.; Amir, M.; Choon Liat, L. (College of Natural Resources, North Carolina State University, 2021)
Entrepreneurs and small and medium enterprises are the foundation of the Malaysian furniture industry. Yet, in a multi-ethnic society such as Malaysia, the success factors of entrepreneurs and small and medium enterprises (SMEs) in the furniture industry have not been studied. Therefore, this study evaluated the success factors of entrepreneurs of the Malay and Chinese ethnic groups in the furniture industry and discerned the growth trajectory of young entrepreneurs from wood science and technology programs in the furniture industry. A questionnaire-based survey was used with the assistance of relevant trade associations and universities. The results were statistically analyzed to establish the significant differences between the two ethnic groups in their perceived success factors. The results revealed that Malay entrepreneurs pay more attention to political and socio-cultural factors to gain success, whereas Chinese entrepreneurs focus on enhancing their competitiveness to remain viable. Further, young graduates showed a reduced desire to pursue a career in the furniture industry, as they deem it not environmentally sustainable in addition to limited career growth. These results suggested that current entrepreneurship development programs may need to be revised, so as to assist in producing more resilient and successful entrepreneurs in the future in the furniture industry.